Water and wastewater technology - Hammer, Mark J. Sr.; Hammer, Mark J., Jr. (India : Pearson Education, Incorporated, 2017)
Comprehensive coverage of such topics as: Water processing; Water distribution; Wastewater collection; Conventional and advanced wastewater treatment; Sludge processing. Key and New Features include: Coverage of new technologies; Water supply and water sustainability woven throughout; Coverage of energy reduction opportunities, and other processes important to water sustainability; Extensive use of illustrations to explain concepts and demonstrate modern equipment and facilities; Extensive use of charts, diagrams, and tables to make the mathematics more accessible.
1. Introduction -- 2. Chemistry -- 3. Biology -- 4. Hydraulics And Hydrology -- 5. Water Quality -- 6. Water Distribution Systems -- 7. Water Processing -- 8. Operation Of Waterworks -- 9. Wastewater Flows And Characteristics -- 10. Wastewater Collection Systems -- 11. Wastewater Processing -- 12. Wastewater Systems Capacity And Asset Management -- 13. Advanced Wastewater Treatment -- 14. Water Reuse -- 15. Sustainability And Carbon Footprint.
Includes index.
Keywords: SEWAGE DISPOSAL